Perceived Stress in Cancer Patients: An Integrative Review - Firdousa Jan; Maharaj Singh; Syed Nisar (Indian Journal of Psychiatric Nursing)
Cancer is disease that many people fear and despise. Cancer is associated with significant psychological and social morbidity. As a result of the disease, cancer patients can experience physical, emotional, and social stress. One of the key factors linked to cancer initiation, development, and metastasis is perceived stress. The aim of this integrative analysis is to assess the literature on cancer patients' perceptions of stress, its relationship to cancer, and health problems associated with perceived stress in cancer patients. A search of Pub Med, CINAHL, Psycho Data, Springer science direct, and the descriptors level of perceived stress and cancer patients between 2000 and 2020 yielded 24 studies that met the review criteria. The following were the examination questions: (1) What is the relationship between perceived stress and cancer? (2) What health issues are associated with perceived stress in cancer patients? Findings support the prevalence of perceived stress in many cancer patients, as well as its connection to other health concerns. Patients' perceptions of stress are linked to cancer, and their general health is affected. It is critical for nurses to measure perceived stress, recognize stressors, and their effect on cancer patients' health and quality of life. Not only oncology nurses, but also all nurses, will benefit from a better understanding of how patients with various forms of cancer experience stress.